Transgenerational effects of polychlorinated biphenyls: 1. Development and physiology across 3 generations of rats - Jan A. Mennigen; Lindsay M. Thompson; Mandee Bell; Marlen Tellez Santos; Andrea C. Gore (BMC, 2018)
Abstract Background Polychlorinated biphenyls (PCBs) are persistent organic environmental contaminants and known endocrine-disrupting chemicals (EDCs). Previous studies demonstrated that developmental exposure to the weakly estrogenic PCB mixture Aroclor 1221 (A1221) in Sprague-Dawley rats altered sexual development, adult reproductive physiology and body weight. The current study tested the hypothesis that prenatal A1221 exposure not only disrupts these endpoints within an exposed individual's (F1 generation) lifespan, but may also affect subsequent generations (F2-F3). Methods We treated pregnant female rats on embryonic days (E) 16 and E18 with A1221 (1 mg/kg), estradiol benzoate (50 μg/kg, positive estrogenic control), or vehicle (3% DMSO in sesame oil, negative control). Endpoints related to sexually dimorphic developmental trajectories of reproductive and developmental physiology were measured, and as adults, reproductive endocrine status was assessed, in the F1, F2, and F3 generations. Results Significant effects of transgenerational EDCs were found for body weight and serum hormones. The A1221 descendants had significantly higher body weight in the F2-maternal lineage throughout postnatal development, and in F3-maternal lineage animals after weaning. In females, generation- and lineage-specific effects of exposure were found for serum progesterone and estradiol. Specifically, serum progesterone concentrations were lower in F2-A1221 females, and higher in F3-A1221 females, compared to their respective F2- and F3-vehicle counterparts. Serum estradiol concentrations were higher in F3-A1221 than F3-vehicle females. Reproductive and adrenal organ weights, birth outcomes, sex ratio, and estrous cycles, were unaffected. It is notable that effects of A1221 were only sometimes mirrored by the estrogenic control, EB, indicating that the mechanism of action of A1221 was likely via non-estrogenic pathways. Conclusions PCBs caused body weight and hormonal effects in rats that were not observed in the directly exposed F1 offspring, but emerged in F2 and F3 generations. Furthermore, most effects were in the maternal lineage; this may relate to the timing of exposure of the F1 fetuses at E16 and 18, when germline (the future F2 generation) epigenetic changes diverge in the sexes. These results showing transgenerational effects of EDCs have implications for humans, as we are now in the 3rd generation since the Chemical Revolution of the mid-twentieth century, and even banned chemicals such as PCBs have a persistent imprint on the health of our descendants.